Optical system to observe an measure the spectra of a light emitting substrate and plasma in a RF magnetron - Andreas Lich, Julian (2017)
To obtain spectra of a light emitting substrate during the deposition of Terbium (Tb) doped thin films by RF magnetron sputtering, an optomechanical device is developed, constructed and tested. The device is required to enable spatial scans of the substrate plane and the plasma beneath. Thereby, measurements of spatial emission intensity distribution and a separation of the Tb spectrum from the plasma-overlain substrate spectrum shall be possible. After an introduction into theoretical and practical boundary conditions, the system’s requirements are specified, followed by a brief investigation of existing solutions for similar problems. A basic optical prototype system is introduced and analysed. After a discussion and evaluation of part solutions, an optomechanical system is developed, constructed, analysed and compared to the prototype system.